People who living with HIV/AIDS also have a high prevalence of anxiety disorders: a systematic review and meta-analysis - Ji, Jiahao; Zhang, Yang; Ma, Yundong; Jia, Lin; Cai, Miaotian; Li, Zhen; Zhang, Tong; Guo, Caiping (Frontiers in Psychiatry, 2024)
Background An estimated 301 million people worldwide suffer from anxiety disorders. People living with HIV/AIDS (PLWHA) are particularly prone to anxiety disorders that could interfere with the important developmental process in an individual’s development and ultimately result in a wide range of negative mental, physical, and psychosocial consequences, as well as poor quality of life in those population groups. Early intervention for anxiety disorders can reverse some of the physical damage caused by anxiety. However, based on systematic reviews and meta-analyses, the specific prevalence of anxiety disorders in PLWHA remains unknown. Method We conducted a literature search on PubMed, Embase, and Web of Science up to 22 October 2022. A random-effects meta-analysis was used to pool prevalence rates from the included studies. Sensitivity and subgroup analyses were performed to identify the possible sources of heterogeneity and to compare the prevalence estimates across groups. The Joanna Briggs Institute’s Quality Assessment Checklist was used to assess the quality of the included studies. Cochran’s Q and I2 tests were used to assess the between-study heterogeneity. Results Ten studies with a total of 238,570 cases were included for the final analysis. Results showed that 15.5% of HIV/AIDS patients had anxiety disorders. The prevalence was higher in females (20.8%) than males (20.7%). The mean age of PLWHA with anxiety disorders was 46.58 ± 11.15 years in these included studies. The subgroup analyses showed significant higher prevalence in non-heterosexual (32.1%). Conclusion We attempted to quantify literature that could allow for stronger inferences to be made regarding the significantly higher prevalence of anxiety disorders in PLWHA, a finding that suggests the imperativeness of intervention strategies to alleviate suffering and reduce the probable negative ramifications. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42023442219, identifier CRD42023442219.